Dynamic Approach in Predicting Land Production Potential for Rubber: Case Study in East and Northeast Thailand - Pratummintra, Somjate (2000)
Due to environmental limitations in Thailand, rubber tree has been introduced to non-traditional areas, which have poor conditions for tree growth. Land evaluation (LE) techniques are required to solve the problems in locating land suitable for rubber. However, these are limited by some missing parameters. This study aimed to develop a crop model to predict maximum potential rubber yield, and to quantify parameters for water balance equation which has not been done in Thailand before. Twenty three soil profiles in different climatic conditions in the eastern Thailand were chosen to establish a reliable production potential model. This model was then applied to predict the land suitable for rubber production in the Northeast Thailand. The FAO crop model, termed as Radiation-thermal Production Potential (RPP) was used to estimate the potential yield from climatic data. It was found that the estimated yield was poorly correlated with the actual rubber yield. Water balance equation was then introduced to quantify soil physical parameters to be incorporated into the model. The results indicated that: (1) crop evapotranspiration in the East Thailand averaged around 3.4 mm day-1 for mature rubber (>10 years old) and 4.5 mm day-1 for immature rubber; (2) the easily available fraction of soil water (p) was 0.75, and was not influenced by soil texture; and (3) crop coefficient value (Kc) changed throughout the year. The Kc changes from 0.48 to 1.08 depending upon the season and maturity of the tree. The Kc values and percentage of the available water storage were related to the leaf fall period and were used to correct the KLAI factor in the crop model. The leaf fall season is considered as the month following the month when the available water storage becomes less than 25% when the KLAI was 0.6183 (0.7 of the maximum value). During the leaf fall period, the KLAI was 0.4415 (0.5 of the maximum KLAI value). This method of calculating production potential is called Water Limited Production (WPP). It was found that the yield estimated by the WPP was highly correlated with the actual rubber yield (R=0.74-0.93). The loss of tapping days was calculated and this was applied to validate the WPP model. This improved model is called as Maximum Production Potential (MPP). The yield estimated by the MPP was also highly correlated with the actual yield (R=0.81-0.94). Upon application of this model in Northeast Thailand, the dry season was found to be longer than before the model was applied.